Removal of iron from BaTa2O6 ceramic powder produced by high energy milling - (:unkn) unknown (ELSEVIER SCI LTD, 2013)
In order to remove Fe coming from the milling environment, mechanochemically produced BaTa2O6 ceramic powder was leached with 6 and 12 M HCl at 95 degrees C and 105 degrees C for time periods varying between 1 and 15 h. Amount of Fe in leached samples was determined by EDS and XRF. Fe concentration decreased from 10.36% to 1.97-3.16% after leaching indicating a 70-81% decrease in iron. Leaching temperature had a more pronounced effect on iron removal than concentration. Leaching caused the formation of porosities and disintegration of powder which accelerated the iron removal. X-ray diffraction analysis of leached milled powders heat treated between 1000 and 1450 degrees C for 5 h indicated that although iron related phases were formed above 1000 degrees C, single BaTa2O6 phase was obtained at 1425 degrees C having tetragonal tungsten bronze type structure. A possible liquid phase formation above 1300 degrees C led to an increase in grain size and density. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Sintering; Mechanochemical synthesis; Leaching; SEM; MECHANOCHEMICAL SYNTHESIS; TRANSFORMATION; NANOPARTICLES; DEGRADATION